Analysis of difficult concepts in Senior Phase Mathematics baseline assessments: First-year student teachers’ reflections - Adelabu, Folake Modupe; Alex, Jogmol Kalariparampil (Research in Social Sciences and Technology- OpenED Network, 2023)
This paper report on first-year student teachers’ reflections on the difficulty levels of mathematics concepts in the senior phase baseline assessments. This paper emanated after first year student teachers completed the baseline assessments for each of the three grades in the senior phase, Grades 7, 8, and 9. One hundred and sixteen (116) first year mathematics student teachers were included in this study. Data were collected using purposive and convenience sampling methods. This qualitative research adopted a case-study design, using an interpretivist paradigm. Data was collected using an open-ended questionnaire as the research instrument. The questionnaire was designed to determine student teachers’ thoughts about the difficulty levels of concepts of the mathematical content in the baseline assessments. The results of the study revealed that Algebra; Number Pattern; Statistics; Shapes; Geometry; Simplification; Sequences and Series; and Addition and Subtraction of numbers as easy topics to answer, Fractions, Mixed fractions, Factorisation, Probability, and Measurement were topics that were very difficult. The study recommended that teacher educators design instructions that will assist student teachers in constructing senior phase mathematical concepts to improve their understanding of these complex topics in higher education institutions.